2007
DOI: 10.1136/tc.2006.018440
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine pharmacokinetics and subjective effects of three potential reduced exposure products, moist snuff and nicotine lozenge

Abstract: Objective: To compare nicotine pharmacokinetics and subjective effects of three new smokeless tobacco potential reduced exposure products (PREPs; Ariva, Revel and Stonewall) with moist snuff (Copenhagen) and medicinal nicotine (Commit lozenge). Methods: 10 subjects completed a randomised, within-subject, crossover study. Subjects used one product for 30 min at each of the five laboratory sessions. Maximal nicotine concentration (C max ) was determined and area under the concentration time curve (AUC) was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…This suggests that Ariva and Stonewall are effective products to curb withdrawal and craving. In support of this interpretation, we found no changes in overall craving or withdrawal as smokers substituted Ariva/ Stonewall for cigarettes, which is generally consistent with reports from others (Blank, Sams, Weaver, & Eissenberg, 2008;Kotlyar et al, 2007;Mendoza-Baumgart et al, 2007). However, although cigarettes per day significantly decreased among smokers who used Ariva/Stonewall, reduction in CO was less striking (6%), suggesting partial compensation (e.g., inhaling deeper, more frequent puffs) and/or problems with the use of CO as a biomarker of tobacco exposure in this population (see following).…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that Ariva and Stonewall are effective products to curb withdrawal and craving. In support of this interpretation, we found no changes in overall craving or withdrawal as smokers substituted Ariva/ Stonewall for cigarettes, which is generally consistent with reports from others (Blank, Sams, Weaver, & Eissenberg, 2008;Kotlyar et al, 2007;Mendoza-Baumgart et al, 2007). However, although cigarettes per day significantly decreased among smokers who used Ariva/Stonewall, reduction in CO was less striking (6%), suggesting partial compensation (e.g., inhaling deeper, more frequent puffs) and/or problems with the use of CO as a biomarker of tobacco exposure in this population (see following).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, one tablet did not increase plasma nicotine concentration reliably. However, in a study of SLT users (Kotlyar et al, 2007), one tablet produced significant increases in maximum nicotine concentration (Cmax). By way of comparison, a single cigarette can increase mean plasma nicotine concentration by 5-14 ng/ml (Benowitz et al, 1988;Breland et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Some of these products have been analyzed to determine tobacco-specific nitrosamine (TSNA) content, and the mean level of TSNAs in Ariva was lower than that found in Exalt, Revel, and smokeless tobacco products typically marketed in the United States (Stepanov, Jensen, Hatsukami, & Hecht, 2006). Another study examined Ariva's effects in smokeless tobacco (SLT) users and found that one tablet delivered nicotine (Cmax 5 2.7 ng/ml; 95% CI 5 2.0-3.6) and reduced craving over a 30-min period (Kotlyar et al, 2007). However, nicotine exposure may differ in SLT users from that of smokers (Benowitz, Porchet, Sheiner, & Jocob, 1988), Ariva's intended audience.…”
Section: Introductionmentioning
confidence: 88%
“…Their impact on the market has been relatively small so far. Generally , they seem to give rise to lower blood nicotine concentrations ( Gray, Breland, Weaver, & Eissenberg, 2008 ;Kotlyar et al, 2007 ) than the traditional ST products -snus and chewing tobacco. The fi lm is tucked to , for example, the palate and will dissolve by itself , while the stick and the orb (tablet) can be manipulated and sucked.…”
Section: Smokeless T Obaccomentioning
confidence: 99%